2020
DOI: 10.1186/s12872-020-01614-x
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of lymphocyte-to-monocyte ratio in the prognosis of acute coronary syndrome patients: a systematic review and meta-analysis

Abstract: Background: The association between the lymphocyte-to-monocyte ratio (LMR) and prognosis in the patients with acute coronary syndrome (ACS) is not fully understood. We performed this systematic review and meta-analysis to evaluate the correlation between LMR and mortality or major adverse cardiac events (MACE) in patients with ACS. Methods: A systematic search was performed in PubMed, MEDLINE, EMBASE, the Cochrane Library, Scopus, and Web of science. The association between LMR and mortality/MACE was analyzed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
0
25
0
2
Order By: Relevance
“…4 C ), but none of these were significantly different between AIS grades. We also used these inferred proportions to calculate leukocyte ratios, which have been proven clinically useful in multiple diseases and traumas ( Choi et al, 2020 ; Quan et al, 2020 ; Zhao et al, 2020 ). The neutrophil-to-lymphocyte and the lymphocyte-to-monocyte ratios were both significantly different between the three groups (one-way ANOVA P values 0.0009 and 0.0273, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 C ), but none of these were significantly different between AIS grades. We also used these inferred proportions to calculate leukocyte ratios, which have been proven clinically useful in multiple diseases and traumas ( Choi et al, 2020 ; Quan et al, 2020 ; Zhao et al, 2020 ). The neutrophil-to-lymphocyte and the lymphocyte-to-monocyte ratios were both significantly different between the three groups (one-way ANOVA P values 0.0009 and 0.0273, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In last meta-analysis, with enrolment of 5 studies comprising 4343 patients to investigate the prognostic value of the LMR in patients with ACS, lower LMR was associated with higher long-term mortality/MACE in patients with ACS [9]. No difference in LMR parameters between patients with ACS and healthy persons was observed in our trial.…”
Section: Introductionmentioning
confidence: 62%
“…Because the LMR combines two kinds of immune cells, it has long been used as an indicator of the condition and treatment of cancer patients [ 22 , 23 ]. In recent years, studies have shown that the LMR is related to stable angina [ 17 , 18 ], acute coronary syndrome (ACS) [[[[ 24 ]]]] and CSF [ 6 ], and it can even be used as an independent predictor of major adverse cardiac events (MACEs) [ 20 , 21 , 24 ]. Yildirim et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%